2017
DOI: 10.1556/004.2017.042
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone concentration, pregnancy and calving rate in Simmental dairy cows after oestrus synchronisation and hCG treatment during the early luteal phase

Abstract: Early embryonic development may be negatively affected by insufficient progesterone (P4) production. Therefore, the aim of our study was to increase P4 by gonadotropin-releasing hormone (GnRH) and/or human chorionic gonadotropin (hCG) treatments after inducing oestrus by prostaglandin (PG) treatment. Lactating Simmental dairy cows (n = 110), between 1 to 5 lactations, with an average milk production of 6,500 1/305 days, at 40-80 days postpartum were used and grouped as follows: (1) PG + GnRH treatment at AI (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…We found administration of hCG after AI has not consistently increased conception rates to AI. Although, previous reports indicate that supplementation of hCG 7 days after AI is beneficial for early CL development, effectively maintaining the pregnancies and leading to an increase in the calving rate and reducing embryo loss 25 . The present results showed that injecting hCG at 5 days after AI could not significantly improve the conception rate even though serum P4 concentration on both days 10 and 45 was greater in the MT + hCG group than in the CTR group 41 .…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We found administration of hCG after AI has not consistently increased conception rates to AI. Although, previous reports indicate that supplementation of hCG 7 days after AI is beneficial for early CL development, effectively maintaining the pregnancies and leading to an increase in the calving rate and reducing embryo loss 25 . The present results showed that injecting hCG at 5 days after AI could not significantly improve the conception rate even though serum P4 concentration on both days 10 and 45 was greater in the MT + hCG group than in the CTR group 41 .…”
Section: Discussioncontrasting
confidence: 79%
“…Administration of human chorionic gonadotropin (hCG) on day 5 after oestrus induces the formation of an accessory corpus luteum (CL) while increasing the concentration of P4 from day 7 24 . Supplementation of hCG after AI is beneficial to early CL development and effectively maintains the pregnancy, increasing the calving rate and reducing embryonic loss 25 . Despite the potential benefits of supplementing with melatonin during AI, its effects on fertility of beef cattle inseminated at a synchronised oestrus have not yet been studied.…”
mentioning
confidence: 99%
“…Other studies have shown that administration of natural sequence GnRH, GnRH agonists or hCG after AI can stimulate CL function which induces accessory CL formation, increases progesterone concentration, and reduces oestradiol production with a consequent positive effect on embryonic survival (Thatcher et al, 2003). Administration of GnRH, a GnRH agonist or hCG after AI at specific times, coincident with the presence of the dominant follicle of the first and second follicular waves, may stimulate CL function, induce accessory CL formation, increase progesterone concentration (Schmitt et al, 1996a, Stevenson et al, 2007 and reduce oestrogen production with a consequent positive effect on pregnancy rate or embryo survival (Thatcher et al, 2003;Šuluburić et al, 2017). Several studies have investigated the effects of GnRH administered during mid-estrous cycle (day 12, 13 or 14 after AI) (Szenci et al, 2006;Lopez-Gatius et al, 2006).…”
Section: Introductionmentioning
confidence: 99%